EUS features and clinical outcomes of gastric calcifying fibrous tumor: a retrospective analysis of 20 cases - Bing Bai; Qiuyu Liu; Bingxi Zhou; Baosong Liang; Shengli Kuang (Frontiers in Oncology, 2026)
Objective To analyze the endoscopic ultrasonography (EUS) features and clinical characteristics of gastric calcifying fibrous tumor (GCFT) to improve the endoscopic recognition of this entity. Methods A retrospective analysis was conducted on 20 consecutive patients with pathologically confirmed GCFT at Henan Provincial People’s Hospital from January 2018 to May 2025. EUS findings and clinical data were reviewed to summarize the endoscopic and clinical features of this rare lesion. Results Of the 20 patients, 12 (60.0%) were female, and 8 (40.0%) were male, with a mean age of 46.65 years (range: 29–62 years). Tumor size ranged from 0.5 to 2.8 cm, with a mean diameter of 1.18 ± 0.55 cm. Most tumors were located in the gastric body (n = 16), followed by the fundus (n = 4). On computed tomography, most lesions presented as solid hyperdense nodules within the gastric wall. Endoscopically, all lesions appeared as submucosal tumors with smooth overlying mucosa. Preoperative EUS showed hypoechoic lesions in 19 cases and iso- to hypoechoic lesions in one. All originated from the muscularis propria. Hyperechoic foci, suggestive of calcifications, were observed in 13 lesions (central calcification in 1, peripheral in 12), accompanied by posterior acoustic shadowing. The overlying mucosa and submucosa appeared thickened compared to the surrounding normal layers. All patients underwent endoscopic resection. Histopathologically, tumors consisted of abundant hyalinized collagenous tissue with occasional calcifications and psammoma bodies. The Ki-67 index ranged from <1% to 5%, and immunohistochemical staining was negative for S-100, CD34, CD117, and Desmin. During a follow-up period of 5 to 71 months, no recurrence was observed. Conclusion GCFT typically presents as a hypoechoic mass originating from the muscularis propria on EUS, frequently accompanied by calcification and deep echo attenuation. These features, when present, may suggest the diagnosis. Endoscopic resection is safe and effective for selected lesions.